2009
DOI: 10.1111/j.1551-2916.2009.03395.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Derived SiOC/ZrO2 Ceramic Nanocomposites with Excellent High‐Temperature Stability

Abstract: Polymer‐derived SiOC/ZrO2 ceramic nanocomposites have been prepared using two synthetic approaches. A commercially available polymethylsilsesquioxane (MK Belsil PMS) was filled with nanocrystalline zirconia particles in the first approach. The second method involved the addition of zirconium tetra(n‐propoxide), Zr(OnPr)4, as zirconia precursor to polysilsesquioxane. The prepared materials have been subsequently cross‐linked and pyrolyzed at 1100°C in argon atmosphere to provide SiOC/ZrO2 ceramics. The obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 26 publications
14
141
0
Order By: Relevance
“…Before describing the ceramization process of the aluminum filled MK polymer with the above mentioned experimental method, we will first summarize briefly the observations gained in the case of pure MK polymer for assessment reasons. The available studies reported in the literature 28,29 show that the polymer-to-ceramic transformation of the polysiloxane MK polymer occurs in three steps and shows a ceramic yield of 86 wt.%. The first weight loss step is due to polycondensation during the cross-linking process and results in the release of H 2 O, ethanol, n-propanol and octamethyl T8 polyhedral oligosilsesquioxane (POSS).…”
Section: Resultsmentioning
confidence: 98%
“…Before describing the ceramization process of the aluminum filled MK polymer with the above mentioned experimental method, we will first summarize briefly the observations gained in the case of pure MK polymer for assessment reasons. The available studies reported in the literature 28,29 show that the polymer-to-ceramic transformation of the polysiloxane MK polymer occurs in three steps and shows a ceramic yield of 86 wt.%. The first weight loss step is due to polycondensation during the cross-linking process and results in the release of H 2 O, ethanol, n-propanol and octamethyl T8 polyhedral oligosilsesquioxane (POSS).…”
Section: Resultsmentioning
confidence: 98%
“…SiC nanowires were grown steadily via a gas-gas reaction when an adequate number of reactant gases were supplied, as shown in the following reaction (1). The SiO and CO gases for the growth of SiC nanowires could be obtained from the following reactions (2)(3)(4). With increasing the content of wood powders, the excess SiO gases were released due to the formation of a large amount of graphite-like carbon, which effected the concentration of SiO and CO gases for the growth of SiC nanowires.…”
Section: Sem and Tem Analysismentioning
confidence: 99%
“…Porous polymer-derived ceramics (PDCs) have recently attracted a lot of interest due to their exceptionally low creep rate, high thermal stability, excellent chemical durability and tunable mechanical properties [1][2][3][4][5], which make PDCs attain the potential applications in catalyst supports, purification of water contaminated with organic dyes, electrodes, supercapacitors, gas storage and drug delivery [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…That is, multiple elements (such as Zr, Mg, Fe, Al and Cu) were introduced in the bonding network of Si-based ceramics [11e13]. For example, ZrO 2 phase was incorporated in SiOC, thus its thermal degradation was increased to 1300 C [14]. ZrO 2 modified SiCN fibers have better oxidation resistance than pure SiCN [15].…”
Section: Introductionmentioning
confidence: 99%